Gestational diabetes: risks, management, and treatment options - Catherine Kim (Dove Medical Press, 2010)
Catherine KimDepartments of Medicine and Obstetrics and Gynecology, University of Michigan, Ann Arbor, MI, USAAbstract: Gestational diabetes mellitus (GDM) is commonly defined as glucose intolerance first recognized during pregnancy. Diagnostic criteria for GDM have changed over the decades, and several definitions are currently used; recent recommendations may increase the prevalence of GDM to as high as one of five pregnancies. Perinatal complications associated with GDM include hypertensive disorders, preterm delivery, shoulder dystocia, stillbirths, clinical neonatal hypoglycemia, hyperbilirubinemia, and cesarean deliveries. Postpartum complications include obesity and impaired glucose tolerance in the offspring and diabetes and cardiovascular disease in the mothers. Management strategies increasingly emphasize optimal management of fetal growth and weight. Monitoring of glucose, fetal stress, and fetal weight through ultrasound combined with maternal weight management, medical nutritional therapy, physical activity, and pharmacotherapy can decrease comorbidities associated with GDM. Consensus is lacking on ideal glucose targets, degree of caloric restriction and content, algorithms for pharmacotherapy, and in particular, the use of oral medications and insulin analogs in lieu of human insulin. Postpartum glucose screening and initiation of healthy lifestyle behaviors, including exercise, adequate fruit and vegetable intake, breastfeeding, and contraception, are encouraged to decrease rates of future glucose intolerance in mothers and offspring.Keywords: glucose intolerance, pregnancy, perinatal complications